Gas permeation through polyethylene glycol/polytetramethylene glycol based polyurethane–silica mixed matrix membranes and interfacial morphology study via modeling approach. Issue 19 (10th March 2023) - Fakhar, Afsaneh; Zarabadipoor, Mohammadmahdi; Talakesh, Mohammad Mehdi; Sadeghi, Morteza
Abstract: A series of mixed matrix membranes (MMMs) based on polyurethane (PU) and silica nanoparticles was fabricated. Three types of PU were synthesized with different polyethylene glycol (PEG)/polytetramethylene glycol ratios (PU0, PU75, and PU100, the corresponding numbers: PEG percent). The MMMs were characterized using FTIR, SEM, and gas permeation measurements (N2, O2, CH4, and CO2 ). The phase mixing of PU0 and PU75 membranes increased with silica content. This resulted in a decrease in gas permeability, while an increase in CO2 /CH4 and CO2 /N2 selectivities. The gas separation trend for PU100 membranes was the opposite. The molecular probing approach was served to study the interfacial structure of the MMMs. The existence of a rigidified polymer layer with 2.38 and 2.44 nm thicknesses around silica was revealed through PU0 and PU75 membranes, respectively. In contrary, silica was surrounded by a polymer chain dilution interphase with a thickness of 2.20 nm for PU100 MMMs. Abstract :